2007
DOI: 10.1080/03323310600950411
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from disability after stroke as a target for a behavioural intervention: Results of a randomized controlled trial

Abstract: A large proportion of intervention participants did not complete the workbook tasks. This was perhaps associated with the fairly low level of personal contact with workbook providers. The modest success of this intervention suggests that it may be possible to develop effective behavioural interventions to enhance recovery from disability in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(158 citation statements)
references
References 53 publications
2
154
0
2
Order By: Relevance
“…Psychological research has established strategies by which control related beliefs can be modified to effect positive change in behaviour (Bandura, 1997). Existing evidence indicates that activity limitations can be reduced in people with impairments, without reducing those impairments, by interventions which increase control beliefs (Fisher & Johnston, 1996;Johnston et al, 2007). These strategies could be incorporated into rehabilitation programmes and intervention protocols to bolster improvements in functional status.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological research has established strategies by which control related beliefs can be modified to effect positive change in behaviour (Bandura, 1997). Existing evidence indicates that activity limitations can be reduced in people with impairments, without reducing those impairments, by interventions which increase control beliefs (Fisher & Johnston, 1996;Johnston et al, 2007). These strategies could be incorporated into rehabilitation programmes and intervention protocols to bolster improvements in functional status.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chronic pain patients in Flor et al's (1992) review, who had improved functioning in everyday tasks despite little change in pain after multidisciplinary treatment, may have undergone changes in their perceived control. Interventions to enhance perceived control have been shown effective in reducing activity limitations in stroke (e.g., Johnston et al, 2007), and perceived control (as self-efficacy) has been targeted in the self-management groups of Lorig and her colleagues, who found that beneficial effects of attendance at their programs were not explained by increased exercise but by greater self-efficacy (Lorig et al, 1989;Lorig & Holman, 1993). …”
Section: Implications For Understanding and Managing Disabilitymentioning
confidence: 99%
“…In addition, while Johnston's (1996) model proposes causal relationships, because of our correlational data we cannot conclude that the relationships are causal. Experimental designs (e.g., Fisher & Johnston, 1996a) and randomized controlled trials (e.g., Johnston et al, 2007) are superior tests of causality.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…However, there are examples of workbooks designed to improve self-efficacy in coronary heart disease 375 and following stroke. 376 In addition, a trial protocol has been published describing an intervention for patients with Huntington's disease that consists of an activity workbook combined with six home visits to promote physical activity and exercise. 377 …”
Section: Comparison With Previous Literaturementioning
confidence: 99%